PENGEMBANGAN INSTRUMEN TES FORMATIF FISIKA KELAS XI SEMESTER GASAL PROGRAM AKSELERASI - Fitrifitanofa, Winda; Waskito, Sutadi; Budiharti, Rini (Jurnal Pendidikan Fisika, 2013)
This research aims to (1) develop a multiple choice formative test for the Odd Semester XI Grade of Acceleration Program corresponding to the existing Standard Competency and Basic Competency, (2) to develop the outline of multiple choice formative test for the Odd Semester XI Grade in Kinematics material with Vector Analysis, Gravitation And Harmonic Movement in Elastic Object, (3) to develop the multiple choice item of for formative test of the Odd Semester XI Grade of Acceleration Program in Kinematics material with Vector Analysis, Gravitation And Harmonic Movement in Elastic Object, and (4) validating the result of formative test instrument development for the Odd Semester XI Grade of Acceleration Program in Kinematics material with Vector Analysis, Gravitation And Harmonic Movement in Elastic Object either qualitatively and quantitatively. This study was a developmental research using Research and Development method. Techniques of analyzing data used were a descriptive qualitative technique with item study by the expert and a quantitative technique using Microsoft Excel program. The test development was done by studying the item by the expert, and then revising its validation. The test instrument consisted of 64 items that had been tried out for its validity. In the smaller group tryout, 40 items had good quality, and 24 items should be revised. The revision of the items with poor quality (24 items) was done continuously until the expert considered that these had been good for being tried out along with the 40 valid items to the larger group. The physics formative test of odd semester XI grade of Acceleration Program that had been developed consisted of 3 material for mid-semester including Kinematics with Vector Analysis, Gravitation And Harmonic Movement in Elastic Object. The instrument development was initiated by making an outline corresponding to the syllabus of National Education Service for the XI grade. The development of outline was also needed to facilitate the administration of student competencyâs track record (authentic assessment).Â  The physics formative test of odd semester XI grader of Acceleration Program that had been validated indicated the test instrument corresponding to the characteristics of good physic test. The test instrument developed had good content validity, high item reliability, for Kinematics with Vector Analysis material (Package 1) had reliability of 0.810710 belonging to very high category, for Gravitation material item (Package 2) had reliability of 0.6844 belonging to high category, and for Harmonic Movement with Elastic Object material had reliability of 0.824764 belonging to very high category. The variance was measured using discrimination index indicating that all results were supported, D > 0,3. The difficulty level of item fell into moderate category 0,3 â¤ P â¤ 0,7, and confounding coefficient functions well. From the development of physics test of the Odd Semester XI Grade of Acceleration Program, 64 items were obtained with good quality. Â  Keywords: development, formative test, Physics for XI grade, Acceleration Program